4′‐Selenonucleosides: Regio‐ and Stereoselective Synthesis of Novel Ribavirin and Acadesine Analogs as Anti‐Hepatitis C Virus (HCV) Agents. Issue 11 (1st October 2021) - Lee, Hyejin; Jarhad, Dnyandev B.; Lee, Ahrim; Lee, Choongho; Jeong, Lak Shin
Abstract: Intrigued by the biological activity of 2′‐ C ‐methylribofuranosyl nucleosides, and ribavirin/acadesine, based on the bioisosteric rationale between oxygen and selenium, we herein report a design and synthesis of the 2′‐ C ‐methyl‐4′‐seleno‐ribavirin and ‐acadesine as potential anti‐HCV agents. The 2′‐ C ‐methyl 4′‐selenoribavirin was synthesized in a regio‐ and stereoselective manner and completely characterized through 2D NMR and X‐ray crystallography. While the 2′‐ C ‐methyl 4′‐selenoacadesine has been efficiently synthesized by utilizing purine‐ring opening/degradation procedure via nucleophilic cleavage of N 3−C2 bond of a purine by ethylenediamine (EDA) as the key step. Abstract : Based on the bioisosteric rationale between oxygen and selenium, we herein report a regio‐ and stereoselective synthesis of the 2′‐C‐methyl‐4′‐seleno‐ribavirin and ‐acadesine as potential anti‐HCV agents.